2016
DOI: 10.1002/arch.21366
|View full text |Cite
|
Sign up to set email alerts
|

The expression patterns of the clock genes period and timeless are affected by photoperiod in the Mediterranean corn stalk borer, Sesamia nonagrioides

Abstract: To obtain clues to the link between the molecular mechanism of circadian and photoperiod clocks, we cloned two circadian clock genes, period (per) and timeless (tim) from the moth Sesamia nonagrioides, which undergoes facultative diapause controlled by photoperiod. Sequence analysis revealed a high degree of conservation among the compared insects fοr both genes. We also investigated the expression patterns of per and tim in brains of larvae growing under 16L:8D (long days), constant darkness (DD) and 10L:14D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In our study ( Figure 5) we showed that the Sncry1 mRNA peaked in the mid night comparable to Snper [11]. The discovery of the existence of two cry genes in moths and butterflies suggested that the clockwork mechanism of Lepidopteran insects differ from that of D. melanogaster [25].…”
Section: The Cryptochrome1 (Cry1) Gene Has Oscillating Expression Undsupporting
confidence: 53%
See 4 more Smart Citations
“…In our study ( Figure 5) we showed that the Sncry1 mRNA peaked in the mid night comparable to Snper [11]. The discovery of the existence of two cry genes in moths and butterflies suggested that the clockwork mechanism of Lepidopteran insects differ from that of D. melanogaster [25].…”
Section: The Cryptochrome1 (Cry1) Gene Has Oscillating Expression Undsupporting
confidence: 53%
“…We speculate that in insects maybe there is another possibility, such as in MCSB, where it seems that CRY1 alone, could evolve dual functions as transcriptional repressor and a photoreceptor. An interesting observation is that Snper, Sntim, Sncyc and Sncry1 synchronously peaked at midnight, revealing [11,12].…”
Section: The Cryptochrome1 (Cry1) Gene Has Oscillating Expression Undmentioning
confidence: 98%
See 3 more Smart Citations